Periodontal tissue destruction caused by an elastic orthodontic spacer: a case report - A. Dannan (Nigerian Dental Association, 2009)
The cooperation between the dentist and the patient is considered to be an important factor in every successful dental treatment, especially in orthodontic treatments in which routine visits are parts of the whole treatment plan. Once this cooperation is lost, possible negative effects may be the consequence. Since the periodontal tissues are mostly affected during orthodontic treatment, resulting in periodontal tissue destruction, it is highly recommended that the patient keeps visiting his/her orthodontist frequently, whether or not he/she will continue the treatment. This case report demonstrates possible features of local periodontal tissue destruction caused by an impacted orthodontic spacer which was noted - or had been ignored - by the patient during a past orthodontic treatment. The poor cooperation between the patient and the orthodontist has been considered the reason for the periodontal tissue destruction in this case. Clinicians should be highly suspicious of any periodontal abnormality that arises when elastic orthodontic spacers are being used in the mouth.